EVALUATION ON THE POPULATION OF STRANGLER FIGS (Ficus subgen. Urostigma) IN MOUNT UNGARAN, CENTRAL JAVA: The Strangler Figs of Ungaran - Firman Heru Kurniawan; Margareta Rahayuningsih; Nugroho Edi Kartijono; Muhammad Abdullah (Media Konservasi, 2022)
A group of the Ficus genus, the strangler figs (Ficus subgen, Urostigma), are known as a more potential as frugivores feed in Mount Ungaran. While the land clearance of the forest into monoculture plantation threats their existence. This study aims to evaluating strangler figs condition by the population study, i.e. densities, distribution, and the demography of each strangler fig species. A total of 25 ha area of Gentong Hill (Northwest part of Mount Ungaran) have been sampled during January-May 2018. We conducted a census of the figs within the sampled area and recorded their life stages in such area. As well as explain the current condition of host tree used by strangler figs in such area. Based on the census that have been conducted, 35 individual belongs to six species strangler figs that equal with 1.4 individual/ha in the value of density is recorded. F. kerkhovenii and the Javan endemic F. involucrata was the commonest species by their densities and abundance. Most of host tree were found dead. The remaining living host tree (16 individuals) are included in three species, i.e. Syzigium antisepticum (14 individual), Weinmannia fraxinea (1 individual), and Engelhardtia spicata (1 individual). Most of the strangler figs found was reached in stage 5 of their life demography, while the stage 1 was the rarest by only 1 individual found. The distribution of strangler figs showed a random pattern. Both of densities and distribution is reasoned by the availability of host tree.